Climate Change Vulnerability in Agriculture Sector: Indexing and Mapping of Four Southern Indian States - G. Sridevi; Amalendu Jyotishi; Sushanta Mahapatra; G. Jagadeesh and Satyasiba Bedamatta
Agriculture is the sector most vulnerable to climate change due to its high dependence on climate and weather conditions. Climate change is a main challenge for agriculture, food security and rural livelihoods for millions of people in India. Among India’s population of more than one billion people, about 68% are directly or indirectly involved in the agricultural sector. This sector is particularly vulnerable to present-day climate variability. In this paper an attempt is made to map and analyze the vulnerability to climate change in different districts of four south Indian states: Andhra Pradesh, Karnataka, Tamil Nadu and Kerala. We have taken five sources of vulnerability indicators: socio-demographic, climatic, agricultural, occupational and common property resources vulnerabilities to compute the composite vulnerability index. The composite vulnerability index suggests that, Adilabad, Chamarajanagar, Thiruvarur and Kasaragod are the most vulnerable districts of Andhra Pradesh, Karnataka, Tamil Nadu and Kerala respectively, whereas Hyderabad, Belgaum, Thoothukkudi, Kottayam are the least vulnerable districts.